PEMODELAN MASALAH TRANSPORTASI DENGAN KOEFISIEN ONGKOS KABUR - Susanto, Sani; Suryadi, Dedy (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
Trasportation problem, elaburates the amount of sources which is able to supplyÂ resources in relation to the capacity limit. In the other side, there are amount ofÂ destinations that need resources supply based on its needs. If the delivery cost for oneÂ unit of resource, from the source to the destination is known, the total delivery cost willÂ be minimum. This article takes a transportation issue in undefinete delivery cost per unit,Â it means, it isnât a single numeral, but takes value from an interval.